Optimalisasi Dana BOS dalam Meningkatkan Kualitas Pembelajaran - Wahyu Muh. Syata; Bellona Mardhatillah Sabillah; Muhammad Juwantho Lewa (Universitas Serambi Mekkah, 2025)
School Operational Assistance (BOS) is one of the government's policies aimed at improving the quality of education in Indonesia through school operational funding. This research aims to analyze the effectiveness of the use of BOS Funds in improving educational standards and to identify the factors that influence the optimization of its utilization. The research method used is a literature review by examining various literature, scientific journals, and relevant research reports. The research results show that the BOS Fund contributes to the provision of educational facilities and infrastructure, the improvement of teacher competencies through training, as well as providing better educational access for students and increasing student learning motivation. However, there are several challenges in the implementation of the BOS Fund, such as delays in fund disbursement, lack of transparency in management, and difficulties for schools in allocating funds according to educational priority needs. Therefore, more effective strategies are needed, including increased transparency, simplification of disbursement procedures, and training for school principals and financial management. With optimal management, the BOS Fund can become a more effective instrument in improving the quality of education in Indonesia.